Children and Young People’s Health Partnership (CYPHP) Evelina London model of care: protocol for an opportunistic cluster randomised controlled trial (cRCT) to assess child health outcomes, healthcare quality and health service use - Michelle Heys; Simon Cousens; Raghu Lingam; Claire Lemer; Ingrid Wolfe; Julia Forman; Rose-Marie Satherley; James Joseph Newham; Mohamed Elsherbiny (BMJ Open)
Introduction Children and young people (CYP) in many high-income settings have poor healthcare outcomes, especially those with long-term conditions (LTCs). Emergency and outpatient hospital service use is increasing unsustainably. To address these problems, the Children and Young People’s Health Partnership (CYPHP) has developed and is evaluating an integrated model of care as part of a health systems strengthening programme across two boroughs of London, UK that are characterised by mixed ethnic populations and varying levels of deprivation. The CYPHP Evelina London model of care comprises proactive case-finding and triage, specialist clinics and transformative education and training for professionals working with CYP. Services are delivered by multidisciplinary health teams with an emphasis on increased coordination across primary, community and hospital settings and integration of physical and mental healthcare that accounts for the CYP’s social context.Methods and analysis The phased roll out of the CYPHP Evelina London model allows an opportunistic population-based evaluation using a cluster randomised controlled trial design. Seventy general practices across two London boroughs, grouped into 23 clusters, were randomised to provide either the CYPHP model of care (n=11) or enhanced usual care (n=12).The evaluation will measure the impact of the CYPHP Evelina London model of care on child and parent health and well-being, healthcare quality and health service use up to 2 years postimplementation. A population-level evaluation will use routinely collected pseudonymised healthcare data to conduct a service-use analysis for all CYP registered with a participating general practice (n=~90 000) with the rate of non-elective admissions as the primary outcome. We will seek consent from a subset of this population, with specific conditions (target n=2138) to assess the impact on patient-reported outcomes using the Paediatric Quality of Life Inventory (PedsQL) and Warwick-Edinburgh Mental Well-Being Scale (WEBWMS) as, respectively, the child- and parent-related primary outcomes.Ethics and dissemination Ethics approval obtained from South West-Cornwall & Plymouth Research Ethics Committee. Results will be submitted for publication in peer-reviewed journals. Findings will be generalisable to community-based models of care, especially in urban settings. Our process evaluation will identify barriers and enablers of implementation and delivery of care salient to the context and condition.Trial registration number NCT03461848; Pre-results.